Integrated Analysis of CD1A Immune Infiltration and Competing Endogenous RNA Networks in COAD - Xu H; Zhang H; Sun S; Zhang J; Huo J; Zhou C (International Journal of General Medicine, 2024)
Houxi Xu,1,2,* Hongqun Zhang,1,3,* Songxian Sun,2,* Jingyuan Zhang,2 Jiege Huo,1,3 Chunxiang Zhou2 1Affiliated Hospital of Integrated Traditional Chinese and Western Medicine, Nanjing, University of Chinese Medicine, Nanjing, People’s Republic of China; 2School of Traditional Chinese Medicine, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China; 3The Third School of Clinical Medicine, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chunxiang Zhou, School of Traditional Chinese Medicine, Nanjing University of Chinese Medicine, Nanjing, 210023, People’s Republic of China, Email chunxiangzhou@njucm.edu.cn Jiege Huo, Affiliated Hospital of Integrated Traditional Chinese and Western Medicine, Nanjing University of Chinese Medicine, Nanjing, 210028, People’s Republic of China, Email huojiege@jsatcm.comBackground: The CD1A gene, a key component of the human immune system and part of the CD1 family, plays a crucial role in presenting lipid antigens to T cells. Abnormal CD1A expression is associated with various immune-related diseases and tumors. However, the biological function of CD1A in COAD is unclear.Methods: Multiple databases were systematically employed to conduct an analysis of CD1A expression in pan-cancer and COAD, along with its clinical-pathological features. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses of CD1A were performed using the ‘clusterProfiler’ package. The Protein-protein interaction (PPI) analysis of CD1A was used the STRING database. Additionally, TIMER and ssGSEA tools were used to explore the relationship between CD1A expression in COAD and immune cell infiltration. The study also investigated the association between CD1A expression and N6-methyladenosine (m6A) modification genes in the TCGA COAD cohort and constructed a CD1A-centric competing endogenous RNA (ceRNA) regulatory network.Results: CD1A displays varying expression levels in various tumors, including COAD, and is closely linked to clinical-pathological characteristics. GO analysis suggests that CD1A plays a role in important processes like antigen processing and presentation, leukocyte-mediated immunity, and lymphocyte-mediated immunity. KEGG analysis identifies CD1A’s involvement in key pathways such as the Chemokine signaling pathway and Cytokine-cytokine receptor interaction. PPI analysis highlights CD1A’s interactions with CD207, CD1C, CD1E, FOXP3, and ITGB2. ssGSEA analysis indicates a significant relationship between CD1A expression and the infiltration of various immune cells in COAD. Significant associations were found between CD1A and m6A modification genes in COAD. Furthermore, a CD1A-centered ceRNA regulatory network has been constructed.Conclusion: CD1A emerges as a potential biomarker for the diagnosis and treatment of COAD, showing a strong association with tumor immune infiltration, m6A modification, and the ceRNA network.Keywords: CD1A, COAD, immune infiltration, m6A, ceRNA